Combining modelling and mutagenesis studies of synaptic vesicle protein 2A to identify a series of residues involved in racetam binding. (21st September 2011) - Shi, Jiye; Anderson, Dina; Lynch, Berkley A.; Castaigne, Jean-Gabriel; Foerch, Patrik; Lebon, Florence
Abstract : LEV (levetiracetam), an antiepileptic drug which possesses a unique profile in animal models of seizure and epilepsy, has as its unique binding site in brain, SV2A (synaptic vesicle protein 2A). Previous studies have used a chimaeric and site-specific mutagenesis approach to identify three residues in the putative tenth transmembrane helix of SV2A that, when mutated, alter binding of LEV and related racetam derivatives to SV2A. In the present paper, we report a combined modelling and mutagenesis study that successfully identifies another 11 residues in SV2A that appear to be involved in ligand binding. Sequence analysis and modelling of SV2A suggested residues equivalent to critical functional residues of other MFS (major facilitator superfamily) transporters. Alanine scanning of these and other SV2A residues resulted in the identification of residues affecting racetam binding, including Ile 273 which differentiated between racetam analogues, when mutated to alanine. Integrating mutagenesis results with docking analysis led to the construction of a mutant in which six SV2A residues were replaced with corresponding SV2B residues. This mutant showed racetam ligand-binding affinity intermediate to the affinities observed for SV2A and SV2B.